Spatially dispersed hydrophobic SiO2 on HZSM-5 zeolite for catalytic upgrading of Bio-oil - Penglong Jia; Rui Yang; Pattreeya Panpian; Zhihua Zhang; Lianfeng Zhu; Yushani Alahakoon; Wei Huang; Jing Wang; Abuliti Abudula; Ye Shui Zhang; Guoqing Guan (Fuel, 2026)

Biomimetic platelet membrane-camouflaged liposomes with RBCs hitchhiking enable efficient targeting and suppression of lung metastasis - Kehui Zhu; Xunyi You; Ke Zhang; Yee Shan Wong; Hong Wang; Rui Zhong; Jiaxin Liu; Ye Cao (Chemical Engineering Journal, 2026)

Short-term nitric oxide gaseous treatment of post-rigor pork: Multidimensional impacts on meat quality, protein oxidation and proteolysis, and microstructure - Jiaye Zhu; Yongmao Ye; Liangyu Zhang; Haoyang Ma; Xinnuo Zhou; Yu Qi; Qingfeng Ge; Mangang Wu; Hai Yu; Rui Liu (Food Chemistry, 2026)

Entropy-driven engineering in AFe2O4 spinel enabling broadband microwave absorption - Xinglai Yuan; Wei Li; Qiancheng Gao; Fan Zhang; Ye Yuan; Xiaohan Wang; Yanqiu Zhu; Mi Tian; Hailong Wang; Rui Zhang; Biao Zhao; Qinghu Wang; et al. (Chemical Engineering Journal, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

Particulate matter concentration and population exposure assessment in metro systems: a case study of Hangzhou - Chen He; Rui Zhang; Xiyao Chen; Keliang Li; Ben Ye; Lingtong Huang; Shupeng Zhu; Weijun Li (Journal of Environmental Sciences, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

A near-infrared AIEgens-based fluorescent probe with large stokes shift for selective lysine detection: Photophysical properties, chirality transmission, and bioimaging applications - Xin Wang; Wenhui Xue; Penghui Xia; Qian Wang; Shizhen Wang; Yuefeng Zhu; Nuo Fei; Keting Zhu; Yuhan Li; Ruimeng Ye; Yang Liu; Zhixin Dong; et al. (Food Chemistry, 2026)

Hyperspectral model for evaluating nitrogen requirements of high-quality indica fragrant rice in South China using the critical nitrogen concentration dilution curve - Yufen Zhang; Feifei Zhu; Zhaowen Mo; Kaiming Liang; Zhanhua Lu; Yibo Chen; Junfeng Pan; Xiangyu Hu; Rui Hu; Meijuan Li; Xinyu Wang; Songpo Duan; et al. (Plant and Soil, 2026)

Design and crashworthiness of a modular discrete re-entrant auxetic honeycomb - Ye Fu; Yilin Zhu; Xue Rui; Shengdong Zhao; Longtao Xie; Chuanzeng Zhang (Engineering Structures, 2026)

Correction to: Long-Term Monochromatic Light Exposure Does Not Alter Modular Chromatic Representation in the Visual Cortex of Rhesus Monkeys - Wenqing Zhu; Ye Liu; Xiaoxiao Chen; Liling Qian; Wei Wang; Leilei Zou; Yiliang Lu; Rui Liu (Neuroscience Bulletin, 2026)

Fluoride-ion mediated radical scavenging in a hydrophobic microenvironment for durable PEM fuel cells - Xuelin Wei; Gang Zhu; Donghao Ye; Aojie Zhang; Hao Zhang; Wangkai Zhu; Tian Tian; Shengqiu Zhao; Jiangping Song; Rui Chen; Haolin Tang (Chemical Engineering Journal, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Recent advances in cerium oxide redox cycle for solar thermochemical hydrogen production - Zilong Feng; Zeai Huang; Ruiyang Zhang; Shan Yu; Gang Feng; Decai Zhou; Guichuan Liu; Jiayi Liu; Ye Zhang; Jin Zhu; Jiarong Zhang; Yong He; et al. (Fuel, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Long-Term Monochromatic Light Exposure Does Not Alter Modular Chromatic Representation in the Visual Cortex of Rhesus Monkeys - Wenqing Zhu; Ye Liu; Xiaoxiao Chen; Liling Qian; Wei Wang; Leilei Zou; Yiliang Lu; Rui Liu (Neuroscience Bulletin, 2026)

Genetic Parameter Estimation of Growth Traits and Their Implications for Selective Breeding in Small Yellow Croaker (Larimichthys Polyactis) - Rui Wang; Jiajie Zhu; Sifang Liu; Ting Ye; Dandan Guo; Yang Liu; Bao Lou; Feng Liu (Marine Biotechnology, 2026)

Structural characterisation of a novel polysaccharide from pseudostellaria heterophylla fibrous root and its anti-inflammatory and antioxidant activities in vitro - Meng-Yu Li; Hai-Tian Deng; Ming-Zhu Ye; Li-Li Lu; Hong-Yuan Chen; Wen Rui (Natural Product Research, 2026)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Leaf-herbivory induced trade-off: Aboveground defense sacrifices root flavonoids to enrich microbes for dual resistance - Junxing Zhang; Chen Ye; Lifen Luo; Yingwei Su; Chenjing Zhao; Yanyan He; Wenjie Luan; Tingshu Yang; Rui Zhang; Bin Chen; Min Yang; Shusheng Zhu (Agriculture, Ecosystems & Environment, 2025)

Eugenol-based meroterpenoids with neural differentiation activity from Eugenia caryophyllata - Cong Yan; Sheng-Rui Yan; Yutong Zhu; Mengjiao Cai; Rui-Li Huang; Xinyu Wang; Shiqing Zhang; Lei Shi; Li-Jun Hu; Wen-Cai Ye; Xiao-Jun Huang; Ying Wang; et al. (Phytochemistry, 2025)

Surface oxygen vacancies and their synergy effect with Pt in Pt/CoCeOx promoting H2 activation for furfural hydrogenation - Yu Fang; Rui Wang; Min Tian; Shanyu Yi; Luna Ruan; Xin Duan; Huan Zhang; Zhiqing Yang; Hengqiang Ye; Lihua Zhu (Chemical Engineering Journal, 2025)

Tailoring reactivity in MOF derivatives via thermally induced amorphization: Synergistic crystalline/amorphous heterointerfaces for efficient 4-nitrophenol detoxification - Wenyao Zhang; Mian Wang; Rui Xiong; Kai Wei; Genping Zhu; Wei Ye; Wei Wang; Haijiao Xie; Peng Gao; Gan Jia (Chemical Engineering Journal, 2025)

An automatic landmarking algorithm for leaf morphology based on conformal mapping - Peige Zhong; Xiaojun Liu; Yulu Ye; Rui Zhang; Hu Zhou; Yan Guo; Baoguo Li; Jinyu Zhu; Yuntao Ma (Computers and Electronics in Agriculture, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

The tumor suppressor SALL2 opposes chemotherapeutic resistance in breast cancer - Qiji Li; Chenxin Li; Yuhao Zhang; Zihan Zheng; Yun Wang; Yingqian Yang; Qingqing Zhu; Rui Wang; Wanhui Xu; Chengming Zhu; Qin Tian; Meng Wang; et al. (Molecular and Cellular Biochemistry, 2025)

Multi-objective optimization and 3E analysis of an integrated PV/T-wind-borehole-ORC driven ground source heat pump system - Manfeng Li; Mengmeng Wang; Kaiyang Zhu; Hailong Li; Rui Ye; Hongyan Shi; Tianbiao He (Process Safety and Environmental Protection, 2025)

ANAC050 confers aluminium resistance by cooperating with secretion of organic acids and accumulation of cell wall hemicelluloses in plants - Ye TAO; Su LI; Yusong LIU; Rui GUO; Changzhao CHEN; Jiu HUANG; Qiang ZHANG; Renfang SHEN; Xiaofang ZHU (Pedosphere, 2025)

Carboxymethyl chitosan/oxidized hyaluronic acid hydrogel-encapsulated hucMSC-derived exosomes for enhanced hepatic regeneration and post-hepatectomy applications - Qiuxia Zheng; Jia Yao; Zongbin Sun; Rui Li; Yue Zhang; Pan Jiang; Ye Xie; Xiaojing Song; Hongfa Sun; Dan Zhu; Haixu Ni; Xun Li (Carbohydrate Polymers, 2025)

Analysis of soil bacterial diversity and effective control of mango anthracnose - Xiaohu Wang; Shuang He; Rui Wang; Xin Liu; Tingting Mo; Qi fei Liu; Liujian Ye; Qixia Zhu; Shengbo Wei; Jianzong Meng; Hongmei Gao; Liqin Zhou (Physiological and Molecular Plant Pathology, 2025)

Experimental investigation on ammonia‑nitrogen adsorption performance of ZSM-5 molecular sieve prepared from coal gangue and fly ash - Qing-Wei Li; Ye-Rui Zhu; Li-Feng Ren; Wen-Ting Xu; Yu-Xin Miao; Yang Xiao; Cai-Ping Wang (Journal of Water Process Engineering, 2025)

High slab thermal gradient facilitates dehydration and megathrust ruptures in the Solomon Sea plate - Weiling Zhu; Yingfeng Ji; Lijun Liu; Rui Qu; Ye Zhu (Journal of Asian Earth Sciences, 2025)

LC-MS/MS-based quantitative method and metrological traceability technology for measuring components of animal origin in beef and lamb and their products - Yuxuan Lu; Rui Zhai; Zhanying Chu; Manman Zhu; Jingjing Li; You Jiang; Zihong Ye (Food Chemistry, 2025)

Surface-Enhanced Raman Scattering (SERS)-based biosensors for advanced extracellular vesicle detection: A review - Rui Fan; Siting Chen; Fei Lan; Wenbin Li; Yitong Zhu; Lifeng Zhang; Ye Zhang; Ling Li (Analytica Chimica Acta, 2025)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Structural defect regulation in corundum-type medium-entropy oxides for enhanced infrared emissivity performance at high temperature - Wenxue Wang; Kang Wang; Songbo Ye; Junsen Hua; Chao Ma; Jinpeng Zhu; Daoyang Han; Hailong Wang; Rui Zhang; Gang Shao (Chemical Engineering Journal, 2024)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

Influence of mountain orientation on precipitation isotopes in the westerly belt of Eurasia - Longhu Chen; Guofeng Zhu; Qin Qin Wang; Linlin Ye; Xinrui Lin; Siyu Lu; Yinying Jiao; Rui Li; Gaojia Meng; Yuhao Wang; Jiangwei Yang; Chen Jia (Global and Planetary Change, 2024)

Strong controlling effect of stress evolution on the 2022 Ms5.0 Honghe earthquake sequence - Ye Zhu; Wenjie Fan; Yingfeng Ji; Weiling Zhu; Lili Feng; Rui Qu (Tectonophysics, 2024)

Development of a superconducting undulator cryostat based on the thermosiphon effect - Xiangzhen Zhang; Miaofu Xu; Zilin Chen; Xiangchen Yang; Tongxian Zhao; Rui Ye; Xiaochen Yang; Xiaojuan Bian; Yao Gao; Huihua Lu; Rui Ge; Zian Zhu; et al. (International Journal of Refrigeration, 2024)

Hypoxia preconditioning of human amniotic mesenchymal stem cells enhances proliferation and migration and promotes their homing via the HGF/C-MET signaling axis to augment the repair of acute liver failure - Qian Wang; Yuwen Li; Hui Yuan; Linya Peng; Zixing Dai; Ye Sun; Rui Liu; Wenting Li; Jun Li; Chuanlong Zhu (Tissue and Cell, 2024)

Parasitoid fitness and quality of Corcyra cephalonica (Stainton) eggs after vacuum packaging combined with cold storage - Ye Zhang; Wenya Zhu; Wenhao Mei; Rui Fan; Juan Wang; Jianzhen Zhang (Journal of Asia-Pacific Entomology, 2024)

Let-7b-TLR7 Signaling Axis Contributes to the Anesthesia/Surgery-Induced Cognitive Impairment - Liyun Deng; Rui Gao; Hai Chen; Bo Jiao; Changteng Zhang; Liuxing Wei; Caiyi Yan; Shixin Ye-Lehmann; Tao Zhu; Chan Chen (Molecular Neurobiology, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

Study on barrier mechanism and application of silico-alkaline sol-modified bentonite cutoff wall materials to lead pollution in lead-zinc tailings pond - Rui Zhu; Changwen Ye; Bo Yu; Weiming Tao; Zhidong Zhou; Jie Li (Journal of Contaminant Hydrology, 2024)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

Integrative analyses of RNA-seq and ChIP-seq Reveal MITF as a Target Gene of TFPI-2 in MDA231 Cells - Guangli Wang; Gaofeng Zhang; Ningxia Zhu; Chunjiang Zhu; Mafei Kang; Guidan Zuo; Zhijie Niu; Wei Ye; Baodong Tian; Rui Cai (Biochemical Genetics, 2023)

Dissipation and movement of soil water in artificial forest in arid oasis areas: Cognition based on stable isotopes - Dongdong Qiu; Guofeng Zhu; Xinrui Lin; Yinying Jiao; Siyu Lu; Jiatong Liu; Jiawei Liu; Wenhao Zhang; Linlin Ye; Rui Li; Qinqin Wang; Longhu Chen (CATENA, 2023)

Identification and characterization of a phosphinothricin N-acetyltransferase from Enterobacter LSJC7 - Feng Zhu; Yu Yan; Xi-mei Xue; Rui-lian Yu; Jun Ye (Pesticide Biochemistry and Physiology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Subduction hydrothermal regime and seismotectonic variation along Kermadec–Tonga megathrusts - Ye Zhu; Yingfeng Ji; Weiling Zhu; Rui Qu; Chaodi Xie; Deng Zeng (Journal of Asian Earth Sciences, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Bioactive icetexane and abietane diterpenes from Isodon phyllopodus - Rui Deng; Juan Zou; Chen-Liang Zhao; Ye-Meng Yang; Chuen Fai Ku; Yu Zhu; Zheng-Ming Liang; Jiang-Hai Ye; Lu-Tai Pan; Hong-Jie Zhang (Natural Product Research, 2023)

Correction to: Methylation and expression quantitative trait locus rs6296 in the HTR1B gene is associated with susceptibility to opioid use disorder - Yunxiao Li; Ye Lu; Qiaoli Xie; Xiaofeng Zeng; Rui Zhang; Wei Dang; Yongsheng Zhu; Jianbo Zhang (Psychopharmacology, 2022)

Methylation and expression quantitative trait locus rs6296 in the HTR1B gene is associated with susceptibility to opioid use disorder - Yunxiao Li; Ye Lu; Qiaoli Xie; Xiaofeng Zeng; Rui Zhang; Wei Dang; Yongsheng Zhu; Jianbo Zhang (Psychopharmacology, 2022)

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Sedimentary Sequence, Evolution Model and Petroleum Geological Significance of Forced Regression: A Case Study of the Miocene Zhujiang Formation of the Pearl River Mouth Basin in the Northern South China Sea - Ye Yu; Linghui Cai; Changmin Zhang; Li Wang; Rui Zhu; Yanran Huang; Taotao Cao (Journal of Marine Science and Engineering, 2021)
Using 2D/3D seismic data and a large number of drilling and logging data and applying sequence stratigraphy, seismic sedimentology, and petroleum geology concepts, the characteristics of the sedimentary sequence of the forced regression have been analysed, the migration trajectory of the coastline have been reconstructed, the evolution model of the forced regression have been presented, and the significance for petroleum geology of the forced regressive sandbodies have been discussed. The falling stage systems tract (FSST) of the Zhujiang Formation present offlap high-angle oblique foreset reflection structure in the seismic profiles of the depositional trends and turbidite fan deposits with strong amplitude mound reflection structure are developed in the downdip direction of its front. The trajectory of migration of the shoreline shows a terraced downtrend in the direction of basin. The FSST is characterized by the shelf-edge delta without topset beds. The FSST was formed in the fall of relative sea-level. Five sets of foreset beds controlled by high-frequency relative eustatic were developed, therefore ordinal regressive overlap can be observed for the five sets of shelf-edge deltas in the depositional trends. The favourable reservoirs which were located close to the upper boundary of the falling stage systems tract and the basal surface of forced regression are sandbodies of the shelf-edge delta front and wave-dominated shoreface sands and the sandbodies of the turbidite fan. Those sandbodies favour the formation of lithologic oil–gas reservoirs by means of good trap sealing conditions, excellent oil–gas reserving performance, and effective oil source communication of fracture system.

Somatic embryogenesis of masson pine (Pinus massoniana): initiation, maturation and genetic stability analysis at SSR loci - Xin-Rui Xia; Fan Yang; Xin Ke; You-Mei Chen; Jian-Ren Ye; Li-Hua Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

Self-Assembled Micelles Improve the Oral Bioavailability of Dihydromyricetin and Anti-Acute Alcoholism Activity - Jing Ye; Sha Bao; Shiying Zhao; Yujing Zhu; Qiao Ren; Rui Li; Xiaohong Xu; Quan Zhang (AAPS PharmSciTech, 2021)

Somatic embryogenesis in slash pine (Pinus elliottii Engelm): improving initiation of embryogenic tissues and maturation of somatic embryos - Fan Yang; Xin-Rui Xia; Xin Ke; Jianren Ye; Li-hua Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Dissecting the Potential of Selenoproteins Extracted from Selenium-Enriched Rice on Physiological, Biochemical and Anti-Ageing Effects In Vivo - Rui Zeng; Muhammad Umer Farooq; Guo Zhang; Zhichen Tang; Tengda Zheng; Yang Su; Sajad Hussain; Yuanke Liang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Biological Trace Element Research, 2020)

Impact of selenium, zinc and their interaction on key enzymes, grain yield, selenium, zinc concentrations, and seedling vigor of biofortified rice - Hla Hla Ei; Tengda Zheng; Muhammad Umer Farooq; Rui Zeng; Yang Su; Yujie Zhang; Yuanke Liang; Zhichen Tang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Environmental Science and Pollution Research, 2020)

Alterations in transcriptome and antioxidant activity of naturally aged mice exposed to selenium-rich rice - Rui Zeng; Yuanke Liang; Muhammad Umer Farooq; Yujie Zhang; Hla Hla Ei; Zhichen Tang; Tengda Zheng; Yang Su; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Environmental Science and Pollution Research, 2019)

Gut microbiota in patients after surgical treatment for colorectal cancer - Ye Jin; Yang Liu; Lei Zhao; Fuya Zhao; Jing Feng; Shengda Li; Huinan Chen; Jiayu Sun; Biqiang Zhu; Rui Geng; Yunwei Wei (Environmental Microbiology, 2019)
Summary Colorectal cancer (CRC) is a common disease worldwide that is strongly associated with the gut microbiota. However, little is known regarding the gut microbiota after surgical treatment. 16S rRNA gene sequencing was used to evaluate differences in gut microbiota among colorectal adenoma patients, CRC patients, CRC postoperative patients and healthy controls by comparing gut microbiota diversity, overall composition and taxonomic signature abundance. The gut microbiota of CRC patients, adenoma patients and healthy controls developed in accordance with the adenoma‐carcinoma sequence, with impressive shifts in the gut microbiota before or during the development of CRC. The gut microbiota of postoperative patients and CRC patients differed significantly. Subdividing CRC postoperative patients according to the presence or absence of newly developed adenoma which based on the colonoscopy findings revealed that the gut microbiota of newly developed adenoma patients differed significantly from that of clean intestine patients and was more similar to the gut microbiota of carcinoma patients than to the gut microbiota of healthy controls. The alterations of the gut microbiota between the two groups of postoperative patients corresponded to CRC prognosis. More importantly, we used the different gut microbiota as biomarkers to distinguish postoperative patients with or without newly developed adenoma, achieving an AUC value of 0.72. These insights on the changes in the gut microbiota of CRC patients after surgical treatment may allow the use of the microbiota as non‐invasive biomarkers for the diagnosis of newly developed adenomas and to help prevent cancer recurrence in postoperative patients.

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

Mechanisms of Acupuncture Therapy for Cerebral Ischemia: an Evidence-Based Review of Clinical and Animal Studies on Cerebral Ischemia - Wen Zhu; Yang Ye; Yi Liu; Xue-Rui Wang; Guang-Xia Shi; Shuai Zhang; Cun-Zhi Liu (Journal of Neuroimmune Pharmacology, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Carboxyamidotriazole alleviates muscle atrophy in tumor-bearing mice by inhibiting NF-κB and activating SIRT1 - Chen Chen; Rui Ju; Lei Zhu; Juan Li; Wei Chen; De-chang Zhang; Cai-ying Ye; Lei Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

Calculation of permissible load capacity and establishment of total amount control in the Wujin River Catchment—a tributary of Taihu Lake, China - Ruibin Zhang; Hailong Gao; Wenting Zhu; Wei Hu; Rui Ye (Environmental Science and Pollution Research, 2015)

Distinctive expression and cellular distribution of dopamine receptors in the pancreatic islets of rats - Ye Chen; Feng Hong; Hui Chen; Rui-Fang Fan; Xiao-Li Zhang; Yue Zhang; Jin-Xia Zhu (Cell and Tissue Research, 2014)

Static corrections methods in the processing of deep reflection seismic data - Xiaosan Zhu; Rui Gao; Qiusheng Li; Ye Guan; Zhanwu Lu; Haiyan Wang (Journal of Earth Science, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

miR-155 inhibits oxidized low-density lipoprotein-induced apoptosis of RAW264.7 cells - Guo-fu Zhu; Li-xia Yang; Rui-wei Guo; Hong Liu; Yan-kun Shi; Hong Wang; Jin-shan Ye; Zhi-hua Yang; Xing Liang (Molecular and Cellular Biochemistry, 2013)

Association of interleukin-1 receptor-associated kinase (IRAK1) gene polymorphisms (rs3027898, rs1059702) with systemic lupus erythematosus in a Chinese Han population - Yu Zhai; Ke Xu; Rui-Xue Leng; Han Cen; Wei Wang; Yan Zhu; Mo Zhou; Chen-Chen Feng; Dong-Qing Ye (Inflammation Research, 2013)

Expression profiles of Th17 pathway related genes in human systemic lupus erythematosus - Hai-Feng Pan; Rui-Xue Leng; Chen-Chen Feng; Xiang-Pei Li; Gui-Mei Chen; Bao-Zhu Li; Wang-Dong Xu; Song Guo Zheng; Dong-Qing Ye (Molecular Biology Reports, 2013)

Association of interleukin 23 receptor gene polymorphisms (rs10489629, rs7517847) with rheumatoid arthritis in European population: a meta-analysis - Yu Zhai; Ke Xu; Fen Huang; Hui Peng; Chen-Chen Feng; Kao-Kao Zhu; Rui-Xue Leng; Hai-Feng Pan; Dong-Qing Ye (Molecular Biology Reports, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Activities and Toxicity of a Novel Plant Growth Regulator 2-Furan-2-yl-[1,3] Dioxolane - Tian Rui Ren; Yan Hong Xie; Wei Wen Zhu; Yong Hong Li; Ye Zhang (Journal of Plant Growth Regulation, 2007)